Actin-Binding Proteins as Potential Biomarkers for Chronic Inflammation-Induced Cancer Diagnosis and Therapy - Yu-Gui Zhang; Jiang-Tao Niu; Hong-Wei Wu; Xin-Lei Si; Shu-Juan Zhang; Dong-Hui Li; Tian-Tian Bian; Yue-Feng Li; Xing-Ke Yan (Analytical Cellular Pathology)
Actin-binding proteins (ABPs), by interacting with actin, regulate the polymerization, depolymerization, bundling, and cross-linking of actin filaments, directly or indirectly, thereby mediating the maintenance of cell morphology, cell movement, and many other biological functions. Consequently, these functions of ABPs help regulate cancer cell invasion and metastasis when cancer occurs. In recent years, a variety of ABPs have been found to be abnormally expressed in various cancers, indicating that the detection and interventions of unusual ABP expression to alter this are available for the treatment of cancer. The early stages of most cancer development involve long-term chronic inflammation or repeated stimulation. This is the case for breast cancer, gastric cancer, lung cancer, prostate cancer, liver cancer, esophageal cancer, pancreatic cancer, melanoma, and colorectal cancer. This article discusses the relationship between chronic inflammation and the above-mentioned cancers, emphatically introduces relevant research on the abnormal expression of ABPs in chronic inflammatory diseases, and reviews research on the expression of different ABPs in the above-mentioned cancers. Furthermore, there is a close relationship between ABP-induced inflammation and cancer. In simple terms, abnormal expression of ABPs contributes to the chronic inflammation developing into cancer. Finally, we provide our viewpoint regarding these unusual ABPs serving as potential biomarkers for chronic inflammation-induced cancer diagnosis and therapy, and interventions to reverse the abnormal expression of ABPs represent a potential approach to preventing or treating the corresponding cancers.